Needles and pillboxes in anisotropic mediums. - Weiglhofer, W.S (IEEE Transactions on antennas and propagation)
We establish a connection between the singularities of dyadic Green functions in biaxial-dielectric media arising from eigenfunction expansions in cylindrical coordinates and general expressions of depolarization dyadics. The results are then extended to general anisotropic-dielectric media